2018
DOI: 10.1016/j.cllc.2017.05.021
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT Overcomes Discordance Between Clinical and Pathologic TNM Classification of Small-size Primary Lung Cancer: Influence on Postoperative Prognosis

Abstract: The concordance rate between c-stage and p-stage for small primary lung cancers had moderate reproducibility. Discordance between c-stage I and p-stage II-IV significantly affected DFS. The maximum standardized uptake value of the primary lesion was an independent prognostic factor, and combining it with c-stage might improve the prediction of therapeutic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…The present study demonstrated that the prognoses of patients with cN1 NSCLC were associated with age, the CEA value, and the primary tumor’s SUVmax value. The primary tumor’s SUVmax value was also an independent prognostic factor for both OS and RFS, which is consistent with previous reports regarding the associations between FDG uptake and tumor malignancy [ 13 16 ]. Clinical and experimental studies have indicated that FDG accumulation during PET examination was correlated with tumor growth rate, cell density, and cell differentiation [ 17 – 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…The present study demonstrated that the prognoses of patients with cN1 NSCLC were associated with age, the CEA value, and the primary tumor’s SUVmax value. The primary tumor’s SUVmax value was also an independent prognostic factor for both OS and RFS, which is consistent with previous reports regarding the associations between FDG uptake and tumor malignancy [ 13 16 ]. Clinical and experimental studies have indicated that FDG accumulation during PET examination was correlated with tumor growth rate, cell density, and cell differentiation [ 17 – 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…SUVmax value was also an independent prognostic factor for both OS and RFS, which is consistent with previous reports on the associations between FDG uptake and tumor malignancy [13][14][15][16]. Clinical and experimental studies have indicated that FDG accumulation during PET examination was correlated with tumor growth rate, cell density, and cell differentiation.…”
supporting
confidence: 91%
“…A recent study proved that the concordance rate between the c-Stage and pathological stage (p-Stage) of the 7th version of the UICC for small lung cancers had moderate reproducibility, and p-Stage but not c-Stage was a significant prognostic indicator of DFS upon multivariate analysis [15]. For c-Stage I NSCLCs, stereotactic radiotherapy (SRT) has been recently shown to confer outcomes comparable with those of surgery [16, 17].…”
Section: Discussionmentioning
confidence: 99%